2023
DOI: 10.1002/cctc.202300813
|View full text |Cite
|
Sign up to set email alerts
|

N,O‐Codoped Onion‐like Carbon Catalyzed Selective Oxidation of Methanol to Dimethoxymethane: Structure‐Activity Relationship

Yunli L. Bai,
Xueya Dai,
Tianlong L. Cao
et al.

Abstract: One‐step synthesis of dimethoxymethane (DMM) via methanol oxidation under the catalysis of nanocarbon is a green and sustainable chemical industrial process. In this work, we successfully prepared nitrogen, oxygen codoped onion‐like carbon (NOLC) via a simple thermal treatment method, which was applied to one‐step synthesis of DMM. The physicochemical characterization results revealed that nitrogen and oxygen elements were successfully introduced into the onion‐like carbon (OLC) catalyst. The proposed NOLC cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…[6,9,58] Very recently, Bai et al reported a metal-free N,O-codoped carbon catalyst for the oxidative dehydrogenation of methanol to DMM with high DMM selectivity of 75 % at low reaction temperature (150 °C) and assigned the acidic and dehydrogenative active sites to carboxylic acid and carbonyl groups of the catalyst, respectively. [59] However, despite the good catalytic performances and technological readiness of the oxidative routes, the loss of valuable H 2 as H 2 O causes low exergy efficiency and high carbon footprint, being the major disadvantage of the established routes. [53,55,60] Besides CO 2 reduction with H 2 to form DMM, which was recently published by Klankermayer and co-workers, [61] the continuous gas-phase nonoxidative dehydrogenation (NOD) of methanol to DMM, with the formation of H 2 instead of H 2 O, is a captivating route for technical implementation.…”
Section: Introductionmentioning
confidence: 99%
“…[6,9,58] Very recently, Bai et al reported a metal-free N,O-codoped carbon catalyst for the oxidative dehydrogenation of methanol to DMM with high DMM selectivity of 75 % at low reaction temperature (150 °C) and assigned the acidic and dehydrogenative active sites to carboxylic acid and carbonyl groups of the catalyst, respectively. [59] However, despite the good catalytic performances and technological readiness of the oxidative routes, the loss of valuable H 2 as H 2 O causes low exergy efficiency and high carbon footprint, being the major disadvantage of the established routes. [53,55,60] Besides CO 2 reduction with H 2 to form DMM, which was recently published by Klankermayer and co-workers, [61] the continuous gas-phase nonoxidative dehydrogenation (NOD) of methanol to DMM, with the formation of H 2 instead of H 2 O, is a captivating route for technical implementation.…”
Section: Introductionmentioning
confidence: 99%